Cytogenetically normal uterine leiomyomas without MED12-mutations: a source to identify unknown mechanisms of the development of uterine smooth muscle tumors - Holzmann, Carsten; Markowski, Dominique Nadine; Koczan, Dirk; Kuepker, Wolfgang; Helmke, Burkhard Maria; Bullerdiek, Jörn (Molecular cytogenetics, 2014)
Recent findings on genetic changes in uterine leiomyomas suggest these benign tumors being a heterogeneous group of diseases in terms of molecular pathogenesis with those showing karyotype alterations as well as those characterized only by cytogenetically invisible mutations of mediator subcomplex 12 (MED12). Herein, five uterine leiomyomas (UL) with an apparently normal karyotype that lacked MED12-mutations were investigated by copy number variation arrays along with their matching myometrium to search for small genomic imbalances. Of five tumors one showed chromothripsis-like phenomena with numerous gains and losses of small segments mainly clustered to five chromosomal regions i.e. 2p14-2pter, 2q33.1-2q37.3, 5q31.3-5qter,11q14.1-11qter, and 18p11.21-18q2.3. Apparently, these cells had escaped detection by classical cytogenetics. Histologically, the tumor presented as a cellular leiomyoma with extended hyalinization. Of the remaining four tumors, one had a small intragenic deletion of the HMGA2 gene that was lacking in the corresponding myometrium. The other three tumors did not show relevant copy number alterations at all. Overall, the results suggest that leiomyomas with an apparently normal karyotype based on classical cytogenetics and lacking MED12 mutations represent a heterogeneous group of diseases. While the HMGA2 deletion detected in one of the tumors likely represents the driver mutation and, due to its size, has escaped detection by classical cytogenetics, the extended genomic imbalances detected in one of the other cases cannot be overlooked by this method suggesting an inability of the affected cells to divide in vitro. Of particular interest in that case is the occurrence of so-called “chromothripsis” or “firestorms” without involvement of the loci of common chromosomal rearrangements in UL, as e.g. 12q14 ~ 15 and 6p21. While chromothripsis was initially described as a hallmark of malignancy, the etiology and significance of this phenomenon in benign tumors still remain obscure. In uterine smooth muscle tumors, these changes per se do not indicate malignancy.
Gesehen am 21.10.2020